Implementation mapping to plan for a hybrid trial testing the effectiveness and implementation of a behavioral intervention for HIV medication adherence and care retention - Hoskins, Katelin; Sanchez, Amanda L.; Hoffacker, Carlin; Momplaisir, Florence; Gross, Robert; Brady, Kathleen A.; Pettit, Amy R.; Zentgraf, Kelly; Mills, Chynna; Coley, DeAuj'Zhane; Beidas, Rinad S. (Frontiers in Public Health, 2022)
Background: Implementation mapping is a systematic, collaborative, and contextually-attentive method for developing implementation strategies. As an exemplar, we applied this method to strategy development for Managed Problem Solving Plus (MAPS+), an adapted evidence-based intervention for HIV medication adherence and care retention that will be delivered by community health workers and tested in an upcoming trial. Methods: In Step 1: Conduct Needs Assessment, we interviewed 31 stakeholders to identify determinants of MAPS+ implementation in 13 clinics serving people with HIV in Philadelphia County. In Step 2: Develop Logic Model, we used these determinants as inputs for a working logic model guided by the Consolidated Framework for Implementation Research. In Step 3: Operationalize Implementation Strategies, our team held a virtual stakeholder meeting to confirm determinants. We synthesized stakeholder feedback, then identified implementation strategies that conceptually matched to determinants using the Expert Recommendations for Implementing Change taxonomy. Next, we operationalized implementation strategies with specific examples for clinic settings. We linked strategies to behavior change theories to allow for a mechanistic understanding. We then held a second virtual stakeholder meeting to present the implementation menu for feedback and glean generalizable insights for how these strategies could be operationalized in each stakeholder’s clinic. In Step 4: Protocolize Strategies, we incorporated stakeholder feedback and finalized the implementation strategy menu. Findings: Implementation mapping produced a menu of 39 strategies including revise professional roles, identify and prepare champions, use warm handoffs, and change record systems. The process of implementation mapping generated key challenges for implementation strategy development: lack of implementation strategies targeting the outer setting (i.e., sociopolitical context); tension between a one-size-fits-all and individualized approach for all clinics; conceptual confusion between facilitators and strategies; and challenges in translating the implementation science lexicon for partners. Implications: This case exemplar advances both MAPS+ implementation and implementation science methods by furthering our understanding of the use of implementation mapping to develop strategies that enhance uptake of evidence-based interventions. The implementation menu will inform MAPS+ deployment across Philadelphia in an upcoming hybrid trial. We will carry out Step 5: Test Strategies to test the effectiveness and implementation of MAPS+.